Students’ Motivation in Playing Volleyball at SMP Negeri 3 Bungku Timur Morowali Regency - Satriana Satriana; Jumain Jumain; Kamarudin Kamarudin; Gunawan Gunawan (Journal of General Education and Humanities, 2025)
The problem in this study is the motivation of students to play volleyball at SMP Negeri 3 Bungku Timur, Morowali Regency. The purpose of this study is to determine the level of motivation among students who play volleyball at SMP Negeri 3 Bungku Timur, Morowali Regency. The sample in this study consisted of 43 people. This study used the total sampling technique. The data collection technique used a survey in the form of a questionnaire. The data analysis technique used descriptive analysis, which was analyzed to draw conclusions through the calculation of the data. The data obtained was analysed using statistical analysis techniques. The results of this study show that 39 students have a very high motivation to play volleyball, with a percentage range of 81.25% to 100%. and four students have motivation in playing volleyball, which is categorised as High with a percentage range of (62.49% - 81.24%). Therefore, it can be concluded that student motivation in playing volleyball at SMP Negeri 3 Bungku Timur, Morowali Regency, is Very High with a percentage range of (81.25% - 100%).